Dimensi Viktimologi Dalam Penanganan Anak Penyalahguna Narkotika Di Indonesia - Widiyaswara, Riani (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
Children as legal subjects have the right to protection, including when dealing with the law as a result of drug abuse. Drug abuse by children is not only a criminal act, but also a social and health problem that victimises children. From a victimology perspective, children who abuse drugs suffer physical, psychological and social harm, and therefore require comprehensive legal protection focused on recovery. This study aims to analyse the forms of legal protection for children who abuse narcotics and the urgency of rehabilitation as the main effort in handling children who are in conflict with the law. This study uses a normative juridical method with a regulatory and conceptual approach, through a literature study of primary, secondary, and tertiary legal materials. The results show that legal protection for children who abuse narcotics includes juridical and non-juridical protection, with medical and social rehabilitation as the main instruments. Imposing criminal sanctions of imprisonment on children who abuse narcotics can have a negative impact on their mental and social development, which is contrary to the principle of the best interests of the child. Therefore, rehabilitation is the most appropriate and fair form of protection in handling children who abuse narcotics to ensure their recovery and future as the nation's next generation.